Non defect-stabilized thermally stable single-atom catalyst - Rui Lang (Nature Portfolio, 2019)
Developing stable single-atom catalysts (SACs) with a high metal loading remains a challenge due to the difficulty of creating high densities of defects on support materials. Here the authors prepare Pt SACs with high Pt loadings by virtue of strong covalent metal-support interaction, rather than support defects.